Mutation of a single residue promotes gating of vertebrate and invertebrate two-pore domain potassium channels - Ismail Ben Soussia (Nature Portfolio, 2019)
Mutations that modulate the activity of ion channels are essential tools to understand the biophysical determinants that control their gating. Here authors reveal the role played by a single residue in the second transmembrane domain of vertebrate and invertebrate two-pore domain potassium channels.